Memperkukuhkan Institusi Wakaf Di Malaysia Melalui Wakaf Bertempoh - Muhammad Ainul Hakim bin Muhammad Khalil; Hussein Azeemi Abdullah Thaidi; Azman Ab. Rahman; Muhamad Firdaus Ab Rahman (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-PROCEEDING 3rd INTERNATIONAL CONFERENCE OF THE POSTGRADUATE STUDENTS AND ACADEMICS IN SYARIAH AND LAW 2020 (3rd INPAC 2020) "Syariah and Law Approach in Solving Contemporary Issues" Organized by: Faculty of Syariah and Law Date: 18 November 2020